2021
DOI: 10.1002/bmc.5121
|View full text |Cite
|
Sign up to set email alerts
|

A simple alternative and improved HPLC method for the estimation of doravirine, lamivudine, and tenofovir disoproxil fumarate in solid oral dosage form

Abstract: A novel method was developed for the simultaneous estimation of the doravirine, lamivudine, and tenofovir disoproxil fumarate in the pharmaceutical dosage form.The chromatogram was run through an Ascentis C18 column (150 Â 4.6 mm, 2.7 μm), with the mobile phase consisting of a phosphate buffer and acetonitrile in the ratio of 50:50 (v/v). The mobile phase was pumped through the column at a flow rate of 1 mL/min. The column temperature was maintained at 30 C. The optimized wavelength for doravirine, lamivudine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The literature search reveals that various analytical techniques have been employed for the quantification of DOR (Doravirine), TDF (Tenofovir disoproxil fumarate), and LMV (Lamivudine), both in combination and individually. Some of the widely used methods include high-performance liquid chromatography (HPLC) and ultraperformance liquid chromatography (UPLC), which have been referenced in several studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Additionally, a high-pressure thin-layer chromatography (HPTLC) method has been reported for the quantification of LMV and TDF alone and in combination [17][18][19][20][21][22][23][24][25][26].…”
Section: Robustnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search reveals that various analytical techniques have been employed for the quantification of DOR (Doravirine), TDF (Tenofovir disoproxil fumarate), and LMV (Lamivudine), both in combination and individually. Some of the widely used methods include high-performance liquid chromatography (HPLC) and ultraperformance liquid chromatography (UPLC), which have been referenced in several studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Additionally, a high-pressure thin-layer chromatography (HPTLC) method has been reported for the quantification of LMV and TDF alone and in combination [17][18][19][20][21][22][23][24][25][26].…”
Section: Robustnessmentioning
confidence: 99%
“…Previous literature searches revealed that various other analytical techniques, such as high-performance liquid chromatography (HPLC) [2][3][4][5][6][7][8][9][10][11][12][13], ultra-performance liquid chromatography (UPLC) [14][15][16], have been employed for the quantification of DOR, TDF, and LMV in combination and alone. High-pressure thin layer chromatography (HPTLC) [17][18][19][20][21][22][23][24][25][26] method has been reported for quantification alone and in combination with LMV and TDF.…”
Section: Introductionmentioning
confidence: 99%
“…As per the literature, it was known that very few analytical methods were identified for doravirine in pharmaceutical formulations such as UV spectroscopic method (Shalin et al, 2011), RP-HPLC methods (Suneetha et al, 2021;Hanuman et al, 2020;Ahamed et al, 2022), UPLC (Tandrima and Shivakumar, 2022) and LC-MS/MS (Ming et al, 2016;Zang and Yang, 2016;Desai et al, 2019). There are some analytical methods that are developed in combination with other drugs (Kokkirala et al, 2021;Godela and Gummadi, 2021;Gollu and Gummadi, 2020). Nonetheless, it became apparent that there was only one UV spectrophotometric method available for assessing doravirine in pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…It was approved by the US Food and Medication Administration in 2018 as a complete drug regimen for HIV type 1 infection in patients who had not previously received antiretroviral therapy [12]. According to the literature, few techniques have been published for estimating Lamivudine, Tenofovir, and Doravirine alone and in combination with various dosage forms utilising UV, HPLC methods [13][14][15]. There is no known technique for determining assay and simultaneous estimate of Lamivudine, Tenofovir, and Doravirine in combination dose form.…”
Section: Introductionmentioning
confidence: 99%